Maternal anemia and red blood cell requirements in 72 women undergoing ex-utero intrapartum treatment (EXIT) procedure - Kloka, Jan Andreas; Jasny, Thomas; Jennewein, Lukas; Friedrichson, Benjamin; Zacharowski, Kai; Neef, Vanessa (Frontiers in Medicine, 2024)
The ex-utero intrapartum treatment (EXIT) allows to ensure fetal airway while keeping uteroplacental circulation. However, EXIT may become a life-threatening procedure due to the increased risk of uterine atony or placenta abruption with increased peripartum blood losses and increased transfusion rates. We aim to review maternal anemia prevalence and transfusion requirements in women undergoing EXIT.Methods: Using data from the Federal German Statistical Office hospitalized women undergoing EXIT between January 1 st 2006 and December 31 st 2021 were included. The prevalence of anemia, peripartum hemorrhage, comorbidities and administration of red blood cells (RBC) transfusion were analyzed.In total, 72 women underwent EXIT with a median maternal age of 31 years (26;33.5). In 43.1% EXIT was conducted at 34-36 weeks of gestational age. "Aneemia during pregnancy" was present in 47.2%, "anemia due to acute bleeding" in 25.0% and "iron deficiency anemia" in 15.3%.Postpartum hemorrhage occurred in 11.1%. RBCs were transfused in 15.3% of all women undergoing EXIT procedure. Most women required 1-5 units of RBCs.Despite the rarity of thise procedure, anemia management and blood conservation strategies in order to reduce the need for RBC transfusion are highly important in women undergoing EXIT procedure.